Conceptual modelling of sustainable Vilnius development - Kaklauskas, Arturas; Zavadskas, Edmundas Kazimieras; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2009)
This research consists of 5 stages: comparative description of the sustainable urban development in developed countries and in Vilnius; a comparison and contrast of sustainable urban development in developed countries and Vilnius; a development of some of the general recommendations as how to improve the efficiency levels for a sustainable Vilnius; submission of particular recommendations for the city of Vilnius; a multiple criteria analysis of sustainable urban development’s components and a selection of the most efficient version of sustainable urban development life cycle. The obtained results have partially confirmed the available data, and interesting trends of the development of established cities have been noted. In order to demonstrate the application of the above research, concrete examples of Vilnius will be considered in this paper. Vilniaus darnaus vystymo konceptualus modeliavimas Santrauka. Šis tyrimas apima penkias pakopas: išsivysčiusių šalių miestų ir Vilniaus darnaus vystymosi lyginamasis aprašymas; išsivysčiusių šalių miestų ir Vilniaus darnaus vystymosi skirtumų nustatymas; bendrų pasiūlymų, kaip pagerinti Vilniaus darnos lygį, kūrimas; konkrečių pasiūlymų pateikimas Vilniaus miestui; miestų darnaus vystymosi komponentų daugiakriterinė analizė ir efektyviausio miesto darnaus vystymosi gyvavimo ciklo varianto parinkimas. Tyrimų rezultatus iš dalies patvirtina turimi duomenys, aprašytos kai kurios žinomų miestų vystymosi tendencijos. Tyrimas iliustruojamas Vilniaus pavyzdžiu. Reikšminiai žodžiai: darnus miestų vystymasis, globalinės vystymosi tendencijos, alternatyvos, Vilnius, konceptualus modeliavimas. First published online: 21 Oct 2010